Examining the impacts of elevated, variable pCO2 on larval Pacific razor clams (Siliqua patula) in Alaska - Alcantar, Marina W.; Hetrick, Jeff; Ramsay, Jacqueline; Kelley, Amanda L. (Frontiers in Marine Science, 2024)
An increase in anthropogenic carbon dioxide is driving oceanic chemical shifts resulting in a long-term global decrease in ocean pH, colloquially termed ocean acidification (OA). Previous studies have demonstrated that OA can have negative physiological consequences for calcifying organisms, especially during early life-history stages. However, much of the previous research has focused on static exposure to future OA conditions, rather than variable exposure to elevated pCO2, which is more ecologically relevant for nearshore species. This study examines the effects of OA on embryonic and larval Pacific razor clams (Siliqua patula), a bivalve that produces a concretion during early shell development. Larvae were spawned and cultured over 28 days under three pCO2 treatments: a static high pCO2 of 867 μatm, a variable, diel pCO2 of 357 to 867 μatm, and an ambient pCO2 of 357 μatm. Our results indicate that the calcium carbonate polymorphism of the concretion phase of S. patula was amorphous calcium carbonate which transitioned to vaterite during the advanced D-veliger stage, with a final polymorphic shift to aragonite in adults, suggesting an increased vulnerability to dissolution under OA. However, exposure to elevated pCO2 appeared to accelerate the transition of larval S. patula from the concretion stage of shell development to complete calcification. There was no significant impact of OA exposure to elevated or variable pCO2 conditions on S. patula growth or HSP70 and calmodulin gene expression. This is the first experimental study examining the response of a concretion producing bivalve to future predicted OA conditions and has important implications for experimentation on larval mollusks and bivalve management.